Analysis of waste processing technologies by composting method - Скляр, Олександр Григорович; Скляр, Александр Григорьевич; Skliar, Oleksandr; Скляр, Радміла Вікторівна; Скляр, Радмила Викторовна; Skliar, Radmila; Jakubowski, T. (My University, 2021)
Regular technological operations with chicken manure are currently developed in Ukraine: quarantine, disinfection and processing. Different methods are used for decontamination of manure: biothermal, thermal, chemical, physical and others.
Keywords: chicken manure; composting; vermicomposting; processing by granulation method; anaerobic fermentation